Sex Differences in rt-PA Utilization at Hospitals Treating Stroke: The National Inpatient Sample - Boehme, Amelia K.; Carr, Brendan G.; Kasner, Scott Eric; Albright, Karen C.; Kallan, Michael J.; Elkind, Mitchell S. V.; Branas, Charles C.; Mullen, Michael T. (Frontiers in Neurology, 2017)
Background and Purpose: Sex and race disparities in recombinant tissue plasminogen activator (rt-PA) use have been reported. We sought to explore sex and race differences in the utilization of rt-PA at primary stroke centers (PSCs) compared to non-PSCs across the US. Methods: Data from the National (Nationwide) Inpatient Sample (NIS) 2004-2010 was utilized to assess sex differences in treatment for ischemic stroke in PSCs compared to non-PSCs. Results: There were 304,152 hospitalizations with a primary diagnosis of ischemic stroke between 2004 and 2010 in the analysis: 75,160 (24.7%) patients were evaluated at a PSC. A little over half of the patients evaluated at PSCs were female (53.8%). A lower proportion of women than men received rt-PA at both PSCs (6.8% vs. 7.5%, p<0.001) and non-PSCs (2.3% vs. 2.8%, p<0.001). After adjustment for potential confounders the odds of being treated with rt-PA remained lower for women regardless of presentation to a PSC (OR 0.87, 95% CI (0.81-0.94) or non-PSC (OR 0.88, 95% CI 0.82-0.94). After stratifying by sex and race, the lowest absolute treatment rates were observed in black women (4.4% at PSC, 1.9% at non-PSC). The odds of treatment, relative to white men, was however lowest for white women (PSC OR=0.85, 95% CI 0.78-0.93; non-PSC OR=0.80, 95% CI 0.75-0.85). In the multivariable model, sex did not modify the effect of PSC certification on rt-PA utilization (p-value for interaction =0.58). Conclusion: Women are less likely to receive rt-PA than men at both PSCs and non-PSCs. Absolute treatment rates are lowest in black women, although the relative difference in men and women was greatest for white women.